Coniferous wood of Agathoxylon from the La Matilde Formation, (Middle Jurassic), Santa Cruz, Argentina - Cabral Kloster, Adriana (2018)
In this contribution, four species of Agathoxylon are described from the La Matilde Formation, Gran Bajo de San Julián and central and south-western sectors of Santa Cruz Province, Argentina. Agathoxylon agathioides (Kräusel and Jain) n. comb., Agathoxylon santalense (Sah and Jain) n. comb., Agathoxylon termieri (Attims) Gnaedinger and Herbst, and the new species Agathoxylon santacruzense n. sp. are described based on a detailed description of the secondary xylem. In this work, it was possible to construct scatter plots to elucidate the anatomical differences between the fossil species described on quantitative anatomical data. Comparisons are made with other Agathoxylon species from Gondwana. These parameters can be used to discriminate genera and species of wood found in the same formation, as well as to establish differences/similarities between other taxa described in other formations. Some localities contain innumerable in situ petrified trees, which allowed us to infer that these taxa formed small forests, or local forests, or small forests within a dense forest, which is a habitat coincident with the extant Araucariaceae.